Skip to main content

Section 14.3 More on Rationalizing the Denominator

In Sectionย 8.2, we learned how to rationalize the denominator in simple expressions like \(\frac{1}{\sqrt{2}}\text{.}\) We will briefly review this topic and then extend the concept to the next level.

Figure 14.3.1 Alternative Video Lesson

Subsection 14.3.1 A Review of Rationalizing the Denominator

To remove radicals from the denominator of \(\frac{1}{\sqrt{2}}\text{,}\) we multiply the numerator and denominator by \(\sqrt{2}\text{:}\)

\begin{align*} \frac{1}{\sqrt{2}}\amp=\frac{1}{\sqrt{2}}\multiplyright{\frac{\sqrt{2}}{\sqrt{2}}}\\ \amp=\frac{\sqrt{2}}{2} \end{align*}

We used the property:

\begin{equation*} \sqrt{x}\cdot\sqrt{x}=x,\text{ where }x\text{ is positive} \end{equation*}
Example 14.3.2

Rationalize the denominator of the expressions.

  1. \(\frac{3}{\sqrt{6}}\)

  2. \(\frac{\sqrt{5}}{\sqrt{72}}\)

Explanation
  1. To rationalize the denominator of \(\frac{3}{\sqrt{6}}\text{,}\) we take the expression and multiply by a special version of \(\highlight{1}\) to make the radical in the denominator cancel.

    \begin{align*} \frac{3}{\sqrt{6}}\amp=\frac{3}{\sqrt{6}}\multiplyright{\frac{\sqrt{6}}{\sqrt{6}}}\\ \amp=\frac{3\sqrt{6}}{6}\\ \amp=\frac{\sqrt{6}}{2} \end{align*}
  2. Rationalizing the denominator of \(\frac{\sqrt{5}}{\sqrt{72}}\) is slightly trickier. We could go the brute force method and multiply both the numerator and denominator by \(\sqrt{72}\text{,}\) and it would be effective; however, we should note that the \(\sqrt{72}\) in the denominator can be reduced first. This will simplify future algebra.

    \begin{align*} \frac{\sqrt{5}}{\sqrt{72}}\amp=\frac{\sqrt{5}}{\sqrt{36\cdot 2}}\\ \amp=\frac{\sqrt{5}}{\sqrt{36}\cdot\sqrt{2}}\\ \amp=\frac{\sqrt{5}}{6\cdot\sqrt{2}}\\ \end{align*}

    Now all that remains is to multiply the numerator and denominator by \(\sqrt{2}\text{.}\)

    \begin{align*} \amp=\frac{\sqrt{5}}{6\cdot\sqrt{2}}\multiplyright{\frac{\sqrt{2}}{\sqrt{2}}}\\ \amp=\frac{\sqrt{10}}{6\cdot 2}\\ \amp=\frac{\sqrt{10}}{12} \end{align*}

Subsection 14.3.2 Rationalize Denominator with Difference of Squares Formula

How can be remove the radical from the denominator of \(\frac{1}{\sqrt{2}+1}\text{?}\) Let's try multiplying the numerator and denominator by \(\sqrt{2}\text{:}\)

\begin{align*} \frac{1}{\sqrt{2}+1}\amp=\frac{1}{\left(\sqrt{2}+1\right)}\multiplyright{\frac{\sqrt{2}}{\sqrt{2}}}\\ \amp=\frac{\sqrt{2}}{\sqrt{2}\cdot\highlight{\sqrt{2}}+1\cdot\highlight{\sqrt{2}}}\\ \amp=\frac{\sqrt{2}}{2+\sqrt{2}} \end{align*}

We removed one radical from the denominator, but created another. We need to find another method. The difference of squares formula will help:

\begin{equation*} (a+b)(a-b)=a^2-b^2 \end{equation*}

Those two squares in \(a^2-b^2\) can remove square roots. To remove the radical from the denominator of \(\frac{1}{\sqrt{2}+1}\text{,}\) we multiply the numerator and denominator by \(\sqrt{2}-1\text{:}\)

\begin{align*} \frac{1}{\sqrt{2}+1}\amp=\frac{1}{\left(\sqrt{2}+1\right)}\multiplyright{\frac{\left(\sqrt{2}-1\right)}{\left(\sqrt{2}-1\right)}}\\ \amp=\frac{\sqrt{2}-1}{\left(\sqrt{2}\right)^2-(1)^2}\\ \amp=\frac{\sqrt{2}-1}{2-1}\\ \amp=\frac{\sqrt{2}-1}{1}\\ \amp=\sqrt{2}-1 \end{align*}

Let's look at a few more examples.

Example 14.3.3

Rationalize the denominator in \(\frac{\sqrt{7}-\sqrt{2}}{\sqrt{5}+\sqrt{3}}\text{.}\)

Explanation

To remove radicals in \(\sqrt{5}+\sqrt{3}\) with the difference of squares formula, we multiply it with \(\sqrt{5}-\sqrt{3}\text{.}\)

\begin{align*} \frac{\sqrt{7}-\sqrt{2}}{\sqrt{5}+\sqrt{3}}\amp=\frac{\sqrt{7}-\sqrt{2}}{\sqrt{5}+\sqrt{3}}\multiplyright{\frac{\left(\sqrt{5}-\sqrt{3}\right)}{\left(\sqrt{5}-\sqrt{3}\right)}}\\ \amp=\frac{\sqrt{7}\multiplyright{\sqrt{5}}-\sqrt{7}\multiplyright{\sqrt{3}}-\sqrt{2}\multiplyright{\sqrt{5}}-\sqrt{2}\multiplyright{-\sqrt{3}}}{\left(\sqrt{5}\right)^2-\left(\sqrt{3}\right)^2}\\ \amp=\frac{\sqrt{35}-\sqrt{21}-\sqrt{10}+\sqrt{6}}{5-3}\\ \amp=\frac{\sqrt{35}-\sqrt{21}-\sqrt{10}+\sqrt{6}}{2} \end{align*}
Example 14.3.4

Rationalize the denominator in \(\frac{\sqrt{3}}{3-2\sqrt{3}}\text{.}\)

Explanation

To remove the radical in \(3-2\sqrt{3}\) with the difference of squares formula, we multiply it with \(3+2\sqrt{3}\text{.}\)

\begin{align*} \frac{\sqrt{3}}{3-2\sqrt{3}}\amp=\frac{\sqrt{3}}{(3-2\sqrt{3})}\multiplyright{\frac{(3+2\sqrt{3})}{(3+2\sqrt{3})}}\\ \amp=\frac{\multiplyleft{3}\sqrt{3}+\multiplyleft{2\sqrt{3}}\sqrt{3}}{(3)^2-\left(2\sqrt{3}\right)^2}\\ \amp=\frac{3\sqrt{3}+2\cdot 3}{9-2^2\left(\sqrt{3}\right)^2}\\ \amp=\frac{3\sqrt{3}+6}{9-4(3)}\\ \amp=\frac{3\left(\sqrt{3}+2\right)}{9-12}\\ \amp=\frac{3\left(\sqrt{3}+2\right)}{-3}\\ \amp=\frac{\sqrt{3}+2}{-1}\\ \amp=-\sqrt{3}-2 \end{align*}

Subsection 14.3.3 Exercises

Review and Warmup
1

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{1}{\sqrt{6}} = }\)

2

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{1}{\sqrt{7}} = }\)

3

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{30}{\sqrt{10}} = }\)

4

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{20}{\sqrt{10}} = }\)

5

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{1}{{\sqrt{28}}} = }\)

6

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{1}{{\sqrt{45}}} = }\)

7

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{8}{{\sqrt{180}}} = }\)

8

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{9}{{\sqrt{72}}} = }\)

Further Rationalizing a Denominator
9

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{3}{\sqrt{m}} = }\)

10

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \frac{1}{\sqrt{n}} = }\)

11

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \sqrt{\frac{13}{14}} = }\)

12

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \sqrt{\frac{14}{15}} = }\)

13

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \sqrt{\frac{11}{72}} = }\)

14

Rationalize the denominator and simplify the expression.

\(\displaystyle{ \sqrt{\frac{5}{24}} = }\)

Rationalizing the Denominator Using the Difference of Squares Formula
15

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{3}{\sqrt{11}+8}=}\)

16

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{4}{\sqrt{2}+3}=}\)

17

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{5}{\sqrt{17}+6}=}\)

18

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{3}{\sqrt{6}+5}=}\)

19

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{\sqrt{2}-12}{\sqrt{11}+10}=}\)

20

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{\sqrt{5}-13}{\sqrt{13}+8}=}\)

21

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{\sqrt{2}-14}{\sqrt{7}+5}=}\)

22

Rationalize the denominator and simplify the expression.

\(\displaystyle{\dfrac{\sqrt{5}-15}{\sqrt{13}+3}=}\)